2022
DOI: 10.1038/s41467-022-33285-x
|View full text |Cite
|
Sign up to set email alerts
|

USP14 promotes tryptophan metabolism and immune suppression by stabilizing IDO1 in colorectal cancer

Abstract: Indoleamine 2,3 dioxygenase 1 (IDO1) is an attractive target for cancer immunotherapy. However, IDO1 inhibitors have shown disappointing therapeutic efficacy in clinical trials, mainly because of the activation of the aryl hydrocarbon receptor (AhR). Here, we show a post-transcriptional regulatory mechanism of IDO1 regulated by a proteasome-associated deubiquitinating enzyme, USP14, in colorectal cancer (CRC). Overexpression of USP14 promotes tryptophan metabolism and T-cell dysfunction by stabilizing the IDO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 70 publications
0
46
0
1
Order By: Relevance
“…According to earlier research, USP14 is crucial in sti ing antitumor immunity. (Shi et al 2022;Wang et al 2021) A review of the literature revealed no research investigating the molecular processes of carcinogenesis and development, as well as the potential diagnostic and prognostic utility of USP14. Therefore, a pan-cancer analysis of USP14 to explore its potential molecular mechanisms in different tumors is crucial and signi cant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to earlier research, USP14 is crucial in sti ing antitumor immunity. (Shi et al 2022;Wang et al 2021) A review of the literature revealed no research investigating the molecular processes of carcinogenesis and development, as well as the potential diagnostic and prognostic utility of USP14. Therefore, a pan-cancer analysis of USP14 to explore its potential molecular mechanisms in different tumors is crucial and signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…A rising number of studies have revealed that USP14 is implicated in a range of usual signaling pathways linked to cancer, neurological disorders, autophagy, immunological responses, and viral infections. (Shi et al 2022; Wang et al 2021) However, there is still no systematic pan-cancer analysis for USP14.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, tryptophan metabolism is a major metabolic pathway which restricts anti-tumor immunity and promotes intrinsic malignant properties of tumor cells, and considers as a target for cancer immunotherapy. 677 – 679 Tryptophan metabolism changes could result in a series of alterations in tumor microenvironment and tumor cells, and then promote tumor progression. Via hindering DNA repair, small molecule metabolites had accumulated in tumors involved in abnormal metabolism.…”
Section: Functional Targetmentioning
confidence: 99%
“…Interestingly, depletion of USP12 established a tumor-promoting TME due to insufficient deubiquitination of PPM1B and activation of NF-ÎșB in cancer cells, which contributed to desensitization of anti-PD-1 immunotherapy in lung cancer cells ( 82 ). In addition, USP14 stabilized indoleamine 2,3 dioxygenase 1 (IDO1) and enhanced immune suppression in colorectal cancer ( 83 ). Depletion of USP14 promoted anti-PD-1 responsiveness in mice and reversed inhibition of cytotoxic T cells due to inhibition of IDOI ( 83 ).…”
Section: Deubiquitinases Stabilize Pd-1/pd-l1mentioning
confidence: 99%
“…In addition, USP14 stabilized indoleamine 2,3 dioxygenase 1 (IDO1) and enhanced immune suppression in colorectal cancer ( 83 ). Depletion of USP14 promoted anti-PD-1 responsiveness in mice and reversed inhibition of cytotoxic T cells due to inhibition of IDOI ( 83 ).…”
Section: Deubiquitinases Stabilize Pd-1/pd-l1mentioning
confidence: 99%